Diffusion of Website-Based Innovation in Population Services in Pekanbaru City - Muflida, Dea Septiana; Latif, Syahrul Akmal; Febrian, Ranggi Ade (Borong Newinera Publisher, 2025)
The purpose of this study is to determine the innovation of the Integrated Population Service Information System (Sipenduduk) in Population Services at the Population and Civil Registration Service of Pekanbaru City along with its inhibiting factors. The problems in this thesis are the lack of socialization, sipenduduk innovation, and limited knowledge of digital technology from the community. The type of research in writing this thesis is a qualitative descriptive research method in which this study explores and analyzes to provide meaning and significance in solving problems. The data collected are in the form of words, pictures, and not numbers. So that an explanation and description of the research topic can be obtained that is in accordance with the title of the research. This writing consists of primary data, namely research in the form of interviews, documentation, and observation, and secondary data obtained, namely from the results of interviews in the study. The study used Nvivo software to help analyze the research results. The literature review was strengthened by using the VOSviwer application. The results of this study are the lack of socialization carried out by the Population and Civil Registration Service of Pekanbaru City due to limited APBD resulting in a lack of public understanding regarding the website mechanism.